Physiological Response of Agricultural Workers in Rice Farming Operations - Karunanithi, R; Tajuddin, A (Journal of Agricultural Engineering, 2003)
Physiological responses and energy expenditure of male and female agricultural workers in performing different rice farming operations were measured. The energy expenditure of male workers varied from 2.4 to 4.9 kcal/min whereas that of female workers varied from 2.3 to 3.5 kcal/min. Male workers consumed 2 to 10 per cent more energy than female workers for performing the same task. Performing farm operations in puddle field was difficult.